Recent patterns of post-conflict aid: Did donors help sustain peace? - Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2016)
Donor reactions to recent settlements of internal conflicts have been highly diverse, in terms of both overall aid and its sectoral composition. The allocation of post-conflict aid tends to be needs-based by favoring particularly poor countries. There is no conclusive evidence, however, that the allocation was shaped by the severity and type of conflicts prior to settlement. Furthermore, the sustainability of conflict resolution appears to be unrelated to the amount and composition of post-conflict aid. These findings, though based on a limited number of post-conflict episodes, underscore concerns voiced by the OECD and non-governmental organizations that traditional approaches to post-conflict aid are not effective.
Keywords: D74; F35; 330; foreign aid; civil war; conflict resolution